Advokasi Pencegahan Cyberbullying bagi Siswa MAN 1 Kabupaten Tanah Datar - Hazmi, Raju Moh Hazmi; Yunaldi, Wendra; Arman, Zuhdi; Munandar, Syaiful (Lembaga Riset Cendekia, Yayasan Berkah Putera Indonesia, 2023)
This service aims to provide an understanding of cyberbullying which often affects school students. The object of this service is located at MAN 1 Tanah Datar Regency, West Sumatra Province with the target being grade 12 students. From semi-structured interviews, it was found that the students did not know about cyberbullying and its impacts. In fact, they have experienced cyberbullying and admitted to having done it several times. The method for implementing this service consists of 4 (four) stages, namely Stage I analysis of the field situation of the service object, Stage II execution of the service implementation, Stage III discussion and evaluation, and Stage IV publishing the results of the service. The results of the service found that there was not yet sufficient digital literacy to prevent cyberbullying and they did not know that cyberbullying was a type of criminal act. This service contribution is able to increase literacy while providing education and mitigation planning for students.